GEOLOGICAL AND GEOELECTRICAL INVESTIGATION OF DIRIOTE DEPOSITS IN OBIAGU, AMAUBURI, AND UMUNEOCHI AREA, SOUTH-EASTERN NIGERIA – SUGGESTIONS FOR QUARRY SITE - Okenu, Stella C. (FUDMA JOURNAL OF SCIENCES, 2023)
The study employs geological and geo-electrical investigation of diorite deposits in south-eastern Nigeria. It involves geological analysis of outcrops and by measuring the electrical values properties of different subsurface materials. The locations were explored to assess the overburden thickness, downward trend, total diorite mineral resource, and rock grade. The results of the geological investigation showed that the rock is a diorite with a mean density of 2.88 x 103 kg-3, 2.71 x 103 kg-3, 2.82 x 103 kg-3 in Obiagu, Umuneochi, and Amaubiri respectively. The rock found in the area showed visible calcite (CaCO3) veins loaded with olivine and pyrite minerals. From the acquired data using the Schlumberger setup, three to five geo-electric layers were deduced from resistivity software in Amaubiri, Obiagu, and Umuneochi. The volume of the diorite materials in the study locations was estimated using the outcrop length, width, thickness, and density to about 365,850metric tons in Umuneochi, 442,656 metric tons in Obiagu, and 2,745,396metric tons in Amaubiri. The trend of outcrops in these areas is in the NE-SW direction. It is suggested to use the core drilling approach to carefully analyze the subsurface to estimate the precise reserve in these places.